(untitled) (Economics and region, 2019)
The conducted analysis of scientific literature allowed to highlight such strategic decision-making levels as "corporate strategy", "business strategy", "functional strategy", "operational strategy". The existing theoretical approaches to the definition of the category "business strategy" are considered, their importance and role in the activity of the enterprise are disclosed, the main tasks which it must perform at the level of business are formulated. The organizational and economic mechanism of the formation and implementation of the business strategy of the enterprise was improved by specifying the functions and tasks of the subjects of implementation of the business strategy of the enterprise, which allowed to allocate methods, levers, informational and normative support, as well as strategic planning tools at the enterprise. In accordance with the developed mechanism and the logic of applying the reverse order method, the state of the current system of strategic management was analyzed, for example, LLC "Hyundai Center Poltava". The functional blocks of strategic management are isolated, which are not fully activated in this enterprise and accordingly hinder its development. The proposed strategic management at an enterprise should be carried out on the basis of the analogy method. According to it, maps of strategic groups of competing car market enterprises of the Poltava region were constructed, direct competitors of the investigated enterprise and the parameters on which the company has a competitive backlog is determined. In view of the results of the procedures carried out, the author of the article provided the company with practical recommendations for achieving competitive advantages, taking into account the proposed introduction of CRM-system for managing customer relations and expanding the range of sales at the expense of cars working on alternative fuels, namely, electric vehicles. The economic substantiation of the proposed measures and strategic initiatives, which confirm the effectiveness of the proposed measures, has been carried out. On the basis of the foregoing general conclusions about the importance of the formation and implementation of business strategy of the enterprise are made.